DVLA - one of the UK's biggest online retailers: a multichannel story - Rhodes, Andrew (Henry Stewart Talks, 2008)
Scope of DVLA, Research and customer insight, Initial objectives, Partnership, Electronic vehicle licensing, Benefits to customers, Benefits to DVLA, Customers' journey before and now, The interfaces, Customer segmentation, Tax disc segmented customer base, What did we do with segmentation?, Results so far
Archived at 2022/03/17